Potato Fluctuation and Risk Preference of Potato Farming in the Bromo Plateau, Indonesia - Rosihan Asmara; Wenny Mamilianti; Nuhfil Hanani; Moch. Muslich Mustadjab (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
Potato farming in Indonesia is performed in the highlands, has a high production risk due to sloping land topography and steep slopes. In addition, low managerial ability in responding to sources of production risk results in the input allocation producing non-optimal production. This research aims to identify production fluctuation and farmers’ risk preferences, measure the level of technical efficiency, and determine the effect of risk preference on technical efficiency. The respondents in this study are 83 farmers. The Just and Pope risk function is used with a utility function approach to finding farmers’ risk preferences. The stochastic Frontier Cobb Douglas processes technical efficiency measurements. While to find out the influence of the factors that influence efficiency, Tobit regression is used. The analysis shows that the respondent’s behave risk-takers amounted to 62.65%. Respondents have not yet reached technical efficiency with an average level of technical efficiency of 0.774. Education, frequency of counseling and training, the application of terrace systems have a significant positive effect on technical efficiency, while land slope has a significant negative impact. Risk preference isn’t affected by technical efficiency and shows positive signs.